Issues relating to the application of monolithic tuneable laser diodes to multi-species gas detection - Phelan, Richard P. (Trinity College (Dublin, Ireland). School of Physics, 2005)
Tuneable Diode Laser Absorption Spectroscopy (TDLAS) technology for gas sensing has had reliance on, and has benefited from, devices developed for the optical communications sector, namely distributed feedback laser diodes. The range in wavelengths of available DFB lasers coincides with absorption spectra of many gases of environmental and industrial interest. However, since the distributed feedback laser diode has a narrow wavelength tuning range, only one gas can be targeted without changing the laser. The objective of this thesis is to advance the strategic capability required to allow development of TDLAS multi-species gas detection systems using widely tuneable laser diodes recently developed for the telecommunication sector. In this thesis, the application of widely tuneable laser diodes and a single frequency tuneable laser diode to trace gas detection in the near infrared region of the spectrum is reported.
Keywords: Physics, Ph.D.; Ph.D. Trinity College Dublin